PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, GAYA KEPEMIMPINAN DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN PERILAKU TIDAK ETI SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada OPD Kota Dumai) - Astuti Widia; Nur Emrinaldi; Hasan Alamsyah Mudrika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of the effectiveness of internal control,leadership style and compliance with accounting rules towards tendency ofaccounting fraud which is mediated by unethical behavior This study wasconducted at 27 departments in Dumai with 67 respondents The data wereanalyzed by using PLS (Partial Least Square) analysis technique, while themethod of determining the sample is by using purposive sampling method. Theresult shows that effectiveness of internal, leadership style, compliance withaccounting rules control and unethical behavior have direct influence towardtendency of accounting fraud. The influence of effectiveness of internal controland leadership style was significantly affecting the unetichal behavior,Nonetheless, compliance with accounting rules variable do not have influencetoward unethical behavior. The influence of effectiveness of internal, leadershipstyle was significantly affecting the tendency of accounting fraud throughunethical behavior. But, compliance with accounting rules does not havesignificantly affecting to tendency of accounting fraud through unethicalbehavior.Keywords : tendency of accounting fraud, internal control effectiveness,leadership style, compliance with accounting rules, unethicalbehavior.